Anxiety Level Responses Of Nursing Students Who Will Take Competency Tests In Wira Medika Institute Of Health Sciences - Ni Made Nopita Wati; I Gede Juanamasta; Putu Lia Linasari; Putu Darmika (Universitas Respati Yogyakarta, 2020)
Competency test is a process to measure the knowledge level, skills and attitudes that are required for professional standards. Competency test is compulsory to be followed by all health workers as a requirement to obtain a registration certificate letters. This competency test must be followed by all final year student who have been completed their Ners education. Of course, it will lead anxiety to final student because if they do not pass the competency test, they will not get an STR and considered as incompetent. The level of anxiety is a condition that makes Ners student feel uneasy, worried, afraid, and tense when they are about to face the competency test. The level of anxiety categorized by various responses such as effective, cognitive, physiologic, and behavioural. The purpose of this study was to determine the level of anxiety in Ners student at STIKES Wira Medika regarding competency test seen by various responses. This type of study is quantitative with a total sampling of 69 students. The results of this study showed most of the respondents were experiencing mild anxiety with 55 students (79.7%), effective response mostly with mild anxiety as well as 54 students (78.3%), cognitive response mostly in mild anxiety with 69 students (87%) and physiological response with 56 students (81.2%) and the response of attitudes mostly in mild anxiety category with 64 students (92.8%). Based on the results of the study above, it is expected that the level of anxiety can be reduced by giving frequent enrichment questions.